Pengaruh Citra Merek, Kepuasan dan Kualitas Produk Terhadap Loyalitas Pelanggan Pada Lazada di Kota Batam - Siti Jamaliyah; Nur Elfi Husda (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study aims to examine and analyze the influence of brand image, customer satisfaction, and product quality on customer loyalty on the Lazada e-commerce platform in Batam City. The research approach applied is a quantitative method with a descriptive nature, designed to identify and measure the causal relationship between research variables objectively and in a structured manner. The population in this study were Lazada users who reside in Batam City and have experience making repeat purchases. The sample determination was carried out using a purposive sampling technique based on certain criteria, resulting in 100 respondents who were deemed to meet the research analysis needs. The process of collecting and processing data was carried out through a series of statistical tests, including validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing to determine the magnitude of the influence of each independent variable on customer loyalty. The results of the multiple linear regression analysis showed that brand image has a 19.8% influence on customer loyalty, followed by customer satisfaction which contributes 29.9%, and product quality which also plays a role 36.9% in shaping Lazada customer loyalty. Simultaneously, these three variables explained 80.0% of the variation in customer loyalty, as indicated by the coefficient of determination (R2). Based on the t-test and F-test findings, it can be concluded that brand image, customer satisfaction, and product quality, both partially and jointly, significantly influence Lazada customer loyalty in Batam City.